Antimicrobial photodynamic therapy with 5-aminolevulinic acid plus antibiotics: a promising treatment for tibial osteomyelitis caused by drug-resistant bacteria - Zuo, Ju; Kong, Feiyan; Wang, Xiyu; Wang, Tianyu; Zhao, Jianxi; Zhao, Zhanjuan (Frontiers in Pharmacology, 2025)
Osteomyelitis is a severely destructive bone disease caused by microbial infections, and currently, no available treatment effectively controls the infection. 5-Aminolevulinic acid is a second-generation endogenous photosensitizer. This study investigated the efficacy of 5-aminolevulinic acid-mediated photodynamic therapy (ALA-PDT) in combination with antibiotics in the treatment of tibial osteomyelitis in rabbits. The results illustrated that ALA-PDT alone and in combination of antibiotics displayed significant efficacy in treating osteomyelitis. Animals in the photodynamic antimicrobial chemotherapy (PACT) + antibiotics group exhibited a higher survival rate, an improved overall mental status, a lower localized infection rate, and reduced Tang Hui and Norden scores (P < 0.05), indicating less severe bone destruction. Histologically, more strips of lamellar new bone formation and more pronounced periosteal hyperplasia were noted in the PACT + antibiotics group. Micro-computed tomography illustrated that the structural integrity of cortical bone and cancellous bone structure had better continuity and clearer display in the PACT + antibiotics group than in the other groups, and the periosteal reaction in the modeling area was the most obvious. Bone parameter analysis indicated that trabecular thickness, bone volume, and trabeculae volume were significantly higher in the PACT + antibiotics group than in the model and antibiotics groups (P < 0.05). Additionally, trabecular separation was significantly lower in the PACT + antibiotic group than in the other groups (P < 0.05). These findings suggest that the combination of ALA-PDT and antibiotics has a sensitizing therapeutic effect, offering a promising strategy for the clinical treatment of osteomyelitis.